Sparsely Ionizing Diagnostic and Natural Background Radiations are Likely Preventing Cancer and other Genomic-Instability-Associated Diseases - Bobby R. Scott; Jennifer Di Palma (SAGE Publishing, 2007)
Routine diagnostic X-rays (e.g., chest X-rays, mammograms, computed tomography scans) and routine diagnostic nuclear medicine procedures using sparsely ionizing radiation forms (e.g., beta and gamma radiations) stimulate the removal of precancerous neoplastically transformed and other genomically unstable cells from the body (medical radiation hormesis). The indicated radiation hormesis arises because radiation doses above an individual-specific stochastic threshold activate a system of cooperative protective processes that include high-fidelity DNA repair/apoptosis (presumed p53 related), an auxiliary apoptosis process (PAM process) that is presumed p53-independent, and stimulated immunity. These forms of induced protection are called adapted protection because they are associated with the radiation adaptive response. Diagnostic X-ray sources, other sources of sparsely ionizing radiation used in nuclear medicine diagnostic procedures, as well as radioisotope-labeled immunoglobulins could be used in conjunction with apoptosis-sensitizing agents (e.g., the natural phenolic compound resveratrol) in curing existing cancer via low-dose fractionated or low-dose, low-dose-rate therapy (therapeutic radiation hormesis). Evidence is provided to support the existence of both therapeutic (curing existing cancer) and medical (cancer prevention) radiation hormesis. Evidence is also provided demonstrating that exposure to environmental sparsely ionizing radiations, such as gamma rays, protect from cancer occurrence and the occurrence of other diseases via inducing adapted protection (environmental radiation hormesis).